A morphometric reassessment of Roger Duff's Polynesian adze typology. (April 2016) - Shipton, Ceri; Weisler, Marshall; Jacomb, Chris; Clarkson, Chris; Walter, Richard
Abstract: Stone adzes are found throughout the Pacific islands and documenting their diversity is critical to understanding relationships between past human populations. The adze typology devised by Roger Duff half a century ago is the standard across New Zealand and the rest of Polynesia. Here we describe the different types in the Duff system and analyse 148 adzes from the Wairau Bar site, which has a high diversity of complete adzes and is the assemblage that Duff used as the basis of his system. We use Principal Components Analysis of morphometric variables to test the empirical basis of the Duff system — an analytical exercise that should have applicability to typological systems elsewhere. Our results show different Duff types clustering separately to an extent, but there are issues of ambiguity in assigning types. Duff emphasized cross-section shape and the elaboration of the tang. We propose a new classification system that emphasizes technological and functional features of the adzes. There is considerable agreement between Duff's system and ours, as different manufacturing methods create different cross-section shapes, and functional modifications are often related to the adze tang. We describe four main manufacturing methods with functional elaborations, resulting in nine different adze types that are represented by at least 3 specimens each at Wairau Bar. Examples of each of these adze types are illustrated. We also note the presence of 'stitched' edges on some adzes likely resulting from fine punch work. The Wairau Bar adzes are some of the finest examples of knapping skill known anywhere in the world and suggest a high level of craft specialization. Highlights: The widely-used Duff adze typology is reassessed using the Wairau Bar assemblage. A new classification system using technological and functional criteria is proposed. Four main adze types and nine sub-types are described from Wairau Bar. The very fine workmanship of the Wairau Bar adzes indicates craft specialization.